Age-Related Differences in the Anthropometric and Physical Fitness Characteristics of Young Soccer Players: A Cross-Sectional Study - Koulla Parpa; Marcos Michaelides (MDPI AG, 2022)
Considering that most professional academies seek to optimize the early detection and physical development of their younger players, the purpose of this study was to examine the anthropometric and physical fitness characteristics in a large cross-sectional sample of youth soccer players in Eastern Europe, starting from a very young age during their in-season period. Three hundred and thirteen soccer players (n = 313), grouped into eight age categories, participated in the study. On the basis of chronological age, the group categories were: 7 (n = 26), 8 (n = 41), 9 (n = 46), 10 (n = 48), 11 (n = 42), 12 (n = 47), 13 (n = 43), and 14 years old (n = 20). The players underwent an anthropometric evaluation, flexibility, handgrip strength, vertical jump performance, speed, and agility assessments. A one-way multivariate analysis of variance (MANOVA) indicated significant differences in the anthropometric and physical fitness variables based on chronological age (F = 13.40, p < 0.05, Wilk's Λ = 0.08, partial η2 = 0.30). Concurrently, there were significant growth and physical fitness differences even in players born in the same chronological year. It is believed that the results have important practical implications, especially for those involved in youth soccer. Based on our results, coaches should contemplate speed and agility development in training sessions starting from a much younger age, as sprinting while changing directions has been considered an essential prerequisite in soccer.